Survey and genetic diversity of wild Brassica oleracea L. germplasm on the Atlantic coast of France - Maggioni, Lorenzo; Bothmer, Roland von; Poulsen, Gert; Harnstrom Aloisi, Karolina (Springer, 2020)
Field survey of Brassica oleracea growing in the wild in northwestern French coastal areas and AFLP analysis of their genetic diversity and population structure. This study offered the highest level of detail ever presented about the distribution of wild B. oleracea populations along the French Atlantic coast. Populations analysed showed a low level of genetic differentiation. Traditional varieties commonly grown in the same area were not fully distinguishable from the wild populations on a molecular level. The level of genetic diversity of the wild populations was similar to, or lower than that of the cultivated crops.